Assessment of the application for renewal of authorisation of Ecobiol® (Bacillus amyloliquefaciens CECT 5940) as a feed additive for chickens for fattening and its extension of use for chickens reared for laying. (20th February 2020) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kos Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of Ecobiol ® when used as a zootechnical additive in feed for chickens for fattening and chickens reared for laying at 1.0 × 10 9 colony forming units (CFU)/kg feed. Ecobiol ® is the trade name for a feed additive based on Bacillus amyloliquefaciens CECT 5940, currently authorised for use in chickens for fattening. This opinion concerns the renewal of the authorisation of Ecobiol ® for chickens for fattening and the evaluation of the new use with chickens reared for laying. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. The FEEDAP Panel concludes that Ecobiol ® is safe under the current conditions of authorisation for the target species (chickens for fattening and chickens reared for laying), consumers of products from animals fed the additive and the environment. Ecobiol ® is not irritant to skin/eye or a skin sensitiser but should be considered a potential respiratory sensitiser. Due to a high dusting potential, exposure of users by inhalation is likely. There is no need for assessing the efficacy of Ecobiol ® in the context of the renewal of the authorisation. The additive, at the level of 1 × 10 9 CFU/kg feed, has the potential to be efficacious in chickens reared for laying.